Intramural duodenal hematoma related to antivitamin K overdose, an unusual cause of acute pancreatitis: Three case presentations - Elghali, Mohamed Amine; Masoudi, Ikram; Nasri, Salsabil; Ferhi, Fehmi; Hafsa, Ala; Yousef, Sabri (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Elghali MA, Masoudi I, Nasri S, Ferhi F, Hafsa A, Yousef S. Intramural duodenal hematoma related to antivitamin K overdose, an unusual cause of acute pancreatitis: Three case presentations. Turk J Gastroenterol 2019; 30(6): 578-9